PENGARUH HIGH INTENSITY INTERVAL TRAINING TERHADAP DAYA TAHAN VO2MAX PADA ATLET PERSINAS ASAD KABUPATEN BONE - Ian Vanath Alhakim; Alif Aryadi Hardi; Khalid Rijaluddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the effect of High Intensity Interval Training (HIIT) on improving VO2Max endurance among Persinas Asad athletes in Bone Regency. The problem addressed in this research is the need for effective training methods to enhance athletes’ aerobic endurance, particularly VO2Max, which is a fundamental component of physical performance in sports such as pencak silat. The objective of this study is to determine whether HIIT has a significant effect on increasing VOMax endurance. This research employed a quantitative approach using an experimental method. Data were collected through observation and documentation techniques. The results of the study indicate that the implementation of High Intensity Interval Training significantly improves VO2Max endurance in athletes. The findings demonstrate that interval-based training provides a meaningful increase in aerobic capacity, making it an effective alternative training method for enhancing endurance performance. Furthermore, VO2Max is identified as a crucial physiological foundation that supports an athlete’s ability to sustain physical activity over time. Therefore, the application of HIIT can be recommended as an efficient training strategy to improve VO2Max and overall endurance capacity in athletes.